A case of buccal vegetative foreign body difficult to diagnose - Toru Inomata; Jumpei Tanaka; Naruhisa Tanaka; Masao Kurosaka (Elsevier, 2021)
It is not uncommon to experience cases of foreign body migration due to trauma in the orofacial region, and the foreign body is removed at the same time as treatment of the injured part. we report a case of a plant foreign body that was difficult to distinguish from a tumor. A 62-year-old man was admitted to our hospital complaining of swelling in the right cheek. A large elastic hard mass on the right outer cheek was palpable. An excision was performed. The excised specimen contained two pieces encapsulated in a fibrous cap. Histopathological findings, the pieces were vegetative foreign body. After confirming the patient's history of facial trauma, he fell down one year ago and had bleeding from the right cheek, but had left it. The diagnosis of vegetative foreign body invasion is characterized by MRI and is considered useful. Postoperative four years, the facial history is good with no facial paralysis.